SA-4 Treatment in Guinea Pig (Cavy porcellus) for Fracture Left Tibia Fibula - Nimas Ayu Pertiwi (Hemera Zoa, 2018)
Guinea pigs (Cavia porcellus) are South American hystricomorph rodents and monogastric herbivores. They have stocky bodies, delicate short limbs with fragile bones and no tails [1]. The Guinea pig anatomy have short legs and little feet with claws on which front feet have four and back feet have only three. Their charachters active and exploring environment, make some traumas especiallay in joint problem. The injuries such as claws inflammation, musculoskeletal disorder and tibia fibula fractures, which are often oblique and can sometimes be open fractures due to the lack of soft tissue around the bone. This paper reports the case of a complete fracture of the proximal on the left tibia and fibula in a guinea pig treated surgically with an intramedullary pin.